EVALUATING BIOLOGICAL VOLATILITY AGAINST SOCIOECONOMIC RESILIENCE: A COMPARATIVE REVIEW OF CLIMATE-DRIVEN VECTOR EXPANSION AND ANTHROPOGENIC MALARIA RECESSION - Sian Park (International Educational Journal of Science and Engineering, 2026)
Climate change is increasingly recognized as an essential driver of transmission of infectious diseases, particularly for vector-borne illnesses like malaria. While the biological link between rising temperatures and the proliferation of the Anopheles mosquito is well established, the extent to which climate change outweighs anthropogenic factors remains debated. This paper evaluates various facets of the debate by comparing two studies with markedly different methodologies. This paper examines Caminade et al. (2014), which employs predictive computer simulations, and Gething et al. (2010), which uses historical data mapping. The analysis reveals a stark contrast between future predictions and historical records. Caminade’s model forecasts that global warming will lead to the infiltration of malaria into new geographic areas and lengthen transmission seasons. Conversely, Gething’s research demonstrates a global recession of the disease over the last century, largely owing to economic development and public health interventions. However, this paper identifies a critical vulnerability; the “economic shield” described by Gething is unevenly distributed, leaving developing nations especially vulnerable to the biological risks predicted by Caminade. The study concludes that relying on previous records of human agency is insufficient. Instead, a dual strategy is required that simultaneously mitigates emissions to reduce biological pressure and expand healthcare infrastructure in vulnerable regions for more equitable and effective protection against malaria.